Achieving 21% External Quantum Efficiency for Nondoped Solution‐Processed Sky‐Blue Thermally Activated Delayed Fluorescence OLEDs by Means of Multi‐(Donor/Acceptor) Emitter with Through‐Space/‐Bond Charge Transfer. Issue 7 (8th February 2020) - Zheng, Xujun; Huang, Rongjuan; Zhong, Cheng; Xie, Guohua; Ning, Weimin; Huang, Manli; Ni, Fan; Dias, Fernando B.; Yang, Chuluo
Abstract: Although numerous thermally activated delayed fluorescence (TADF) organic light‐emitting diodes (OLEDs) have been demonstrated, efficient blue or even sky‐blue TADF‐based nondoped solution‐processed devices are still very rare. Herein, through‐space charge transfer (TSCT) and through‐bond charge transfer (TBCT) effects are skillfully incorporated, as well as the multi‐(donor/acceptor) characteristic, into one molecule. The former allows this material to show small singlet–triplet energy splitting (Δ E ST ) and a high transition dipole moment. The latter, on the one hand, further lights up multichannel reverse intersystem crossing (RISC) to increase triplet exciton utilization via degenerating molecular orbitals. On the other hand, the nature of the molecular twisted structure effectively suppresses intermolecular packing to obtain high photoluminescence quantum yield (PLQY) in neat flims. Consequently, using this design strategy, T‐CNDF‐T‐ t Cz containing three donor and three acceptor units, successfully realizes a small Δ E ST (≈0.03 eV) and a high PLQY (≈0.76) at the same time; hence the nondoped solution‐processed sky‐blue TADF‐OLED displays record‐breaking efficiency among the solution process‐based nondoped sky‐blue OLEDs, with high brightness over 5200 cd m −2 and external quantum efficiency up to 21.0%. Abstract : A novel multi‐(donor/acceptor) thermally activated delayed fluorescence (TADF) molecule with through‐space/‐bond charge transfer is developed. Its nondoped solution‐processed sky‐blue organic light‐emitting diode (OLED) displays high performance with an external quantum efficiency (EQEmax ) up to 21.0%, which represents the record‐breaking efficiency among the solution process‐based nondoped sky‐blue OLEDs.